HEAVY AND LIGHT BODY PARTS: THE WEIGHING METAPHOR IN EARLY CHINESE DIALOGUES*. (September 2015) - Defoort, Carine
Abstract The article analyses the metaphorical use of weighing body parts such as fingers, arms, or a head. Our understanding of the weighing metaphor has been much influenced by A. C. Graham's characterization of its rhetorical mechanism, followed by Griet Vankeerberghen in her description of one type of weighing (quan B). The basis of this understanding are two corrupt textual fragments in the dialectical chapters of the Mozi. Several Lü shi chunqiu chapters, however, contain a set of argumentative stories in which body parts are weighed in terms of light and heavy. These stories always argue in favor of life and health, they have a relatively consistent structure, and they may have constituted the core of a larger set of related arguments. Insight into their working can therefore enlighten our reading of other texts.